Forschung und Lehre als identitätsstiftendes Ideal Die Darstellung der Universität aus der Innen- und Außenperspektive von 1999-2014 - Bers, Christiana (Universitätsverlag Göttingen, 2018)
How has the university been discussed between scientific mission, study and education since the beginning of the Bologna reform? The study examines this question using 1130 articles published in the weekly newspaper DIE ZEIT and the journal Forschung & Lehre in the period from 1999 to 2014 as examples. Thus, the connection between »research and teaching« as a description of the university tasks and its function to save and create identity, is taken into account. Furthermore, the study debates how university members and outsiders describe and evaluate the development of the university. The predominantly qualitative argumentation analyses repeatedly resort to descriptive-quantitative results to. Hence, both individual argumentation patterns and general debates around the subject of the university of the present are viewed upon.